Leveraging the Human Capital Values and University's Support on Knowledge Transfer Program for Community in Malaysia - Roslinah Mahmud; Roselina Ahmad Saufi; Rosle Mohidin; Noor Fzlinda Fabeil; Rostika Petrus Boroh; Junainah Jaidi; Mariam Firdhaus Mad Nordin (2018)
Community transformation based on economic empowerment is one of most challenging issues faced by the government in ensuring continuous future development in Malaysia. The aspiration to shift from middle-income to high-income community required higher commitment from various stakeholders. Strengthening human capital value required community transformation which reflected in high value-added and knowledge-intensive activities that considered as one of the greatest available resources to heighten the Malaysia strategy in achieving continuous community development. Knowledge Transfer (KT) is declared in the Malaysian government blueprint as one of the program that aims to support the government's efforts to eradicate poverty and embracing community development through the transferring of knowledge, translating theories into practice and skills possess by the academia and graduate interns in the universities to the community at large. A total of 458 knowledge transfer projects were approved by the Malaysian government since 2011 to 2016 and out of that numbers, there are 352 projects under the flagship of community. Due the importance of the community development to the nation at large, the study attempts to investigate the effect of human capital values and University's support on the community development success based on a perception and experience of graduate intern (GI) in handling their KTP projects. Data were collected through structured questionnaires and regression analysis is conducted in this study. The findings reveal that human capital value and university's support are positively related to the community development performance. The result indicates the importance of casting of human capital value and affirmative support from the higher institution of learning (HIL) as an authorized agency in ensuring the success of KTP project.